Talent management, specific for different age generations in Ho Chi Minh City - Nguyen, Lam Nhu Quynh; Legnerová, Kateřina, 1965-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This study explores the landscape of talent management in Ho Chi Minh City (HCMC), Vietnam, within the context of its dynamic economic growth and diverse workforce. It will explain the talent management model and explores the actual situation of human resource management in HCMC. From there, it will point out the challenges and opportunities of talent planning, attracting, and selecting amidst the evolving employment landscape. While exploring the challenges and opportunities of talent management in this setting, the study focuses on the unique characteristics and preferences of Baby Boomers, Generation X, Millennials, and Generation Z. Utilizing a qualitative methodology, the study aims to uncover the reasons behind the limited applicability of talent management theories in reality in HCMC, while emphasizing the challenges incures with Baby Boomers and Generation X and the significance of Millennials and Gen Z in the HCMC workforce. Furthermore, it examines how understanding the characteristics and preferences of different generations in the workforce can inform tailored talent management strategies for enhanced organizational performance. By examining HR practices in Vietnam and their evolution in the absence of formal talent management frameworks, the study seeks to contribute to knowledge by providing insights into effective talent management strategies for organizations operating in developing city environments.
Vedoucí práce: Kateřina Legnerová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses